Realization of Polarization and Malus’s Law Using The Smartphones - Erol, M.; Çolak, İ. Ö. (Jurnal Pendidikan Fisika Indonesia, 2020)
This work provides an approach for simplifying and teaching of the confusing topic of Polarisation of light and relating Malus’s Law. Teaching Polarisation and the Malus’s Law are modestly achieved by means of smartphones with a convenient light meter application. The apparatus is designed so that the polarizer, the analyser, the laser light source and the smartphone are precisely aligned on a rail. During the performance, the angle of the analyser is basically varied with respect to the polariser and the transmitted light intensity is measured by the light meter application. The results clearly show that the transmitted light intensity is directly proportional to the squared polarization angle. The approach surely provides accessibility for physics teachers and would help students to learn and internalize Polarisation and relating Malus’s Law in a better manner.